Assessing the nosocomial infections' rate and the antibiotic resistance pattern among the patient hospitalized in beheshti hospital during 2013 - Manijeh Kadkhodaei; Mohammad Reza Sharif; Mohammad Ali Saba; Gholam Abbass Mousavi (International Archives of Health Sciences, 2018)
Aims: Nosocomial infection is associated with increased mortality, morbidity, and length of stay. Detection of infection, identify the etiology of bacterial antibiotic resistance pattern, is necessary given the widespread use of antibiotics and antibiotic-resistant organisms. Materials and Methods: This cross-sectional study was done on 288 patients admitted to the Beheshti Hospitals in Kashan based on NNIS definitions according to the state of Health and Medical education. In this study infections and antibiotic resistance symptoms were found. Data analyses were performed with Chi-square test. Results: Among the 288 patients studied, with mean out of hospital infection was 0.80%. Most cases of infection associated were pneumonia. The highest rates of infection were in the Intensive Care Unit (ICU) with 51.7%. Nosocomial infection in ICU wards was associated with increased mortality and morbidity. The most common types were ventilator-associated pneumonia. Among the microorganisms, negative Gram was seen more. The common pathogens were including Acinetobacter, Escherichia coli, and Klebsiella. Antimicrobial resistance was generally increasing and had emerged from selective pressure from antibiotic use and transmission through health staff. Conclusion: This study showed a correlation between antibiotic use and resistance of microorganisms is significant. Hence, it seems that reducing aggressive acts and conduct hygiene education and monitoring act of antibiotics is necessary to prevent antibiotic resistance.